A comparison of gait characteristics between posterior stabilized total knee and fixed bearing unicompartmental knee arthroplasties - Kohei Nishizawa; Kengo Harato; Yutaro Morishige; Shu Kobayashi; Yasuo Niki; Takeo Nagura (Elsevier, 2020)
Background/Objective: According to previous studies, physiological gait pattern was found in unicompartmental knee arthroplasty (UKA) as compared to total knee arthroplasty (TKA) concerning the gait parameters including gait speed, cadence, and step length. However, little attention had been paid to the detailed kinematic and kinetic differences during gait between TKAs and UKAs. The aim of the present study was to investigate and to clarify the biomechanical differences between posterior stabilized TKAs and fixed bearing UKAs during walking Methods: A total of 28 patients participated in the present study. Fifteen patients who underwent TKA and thirteen patients who underwent UKA were enrolled. Gait analysis was done at an average of 12.9 months after surgery. The subjects performed level walking at a preferred speed. For each subject, three-dimensional kinematic, kinetic and ground reaction force data were recorded as well as clinical data including range of motion at the knee joint and plain radiographs. Differences of knee kinematics or kinetics were compared between TKAs and UKAs using two-tailed Mann Whitney U-test. Results: On physical examination, passive range motion was significantly smaller in TKAs than in UKAs, while femorotibial angle on plain radiographs was not significantly different on plain radiographs. In terms of kinematics, TKAs were more flexed at heel contact and less extended in mid-stance phase compared to UKAs in the sagittal plane, and total excursion of TKAs were also smaller than UKAs. Regarding knee kinetics, TKA patients had significantly less peak tibial internal rotation moment in terminal stance phase. In addition, peak knee adduction moment was significantly larger in UKAs than in TKAs, while peak knee flexion moment was not significantly different. Conclusion: Posterior stabilized TKAs exhibited less peak tibial internal rotation moment, which is known as pivot shift avoidance gait, in the present study, compared to fixed bearing UKAs. TKAs had similar gait pattern to anterior cruciate ligament deficient knees, compared to UKAs even if patients with TKAs had no subjective pain during walking.